Development Strategies and the Impact of Marine Tourism on the Socio-Economic Conditions of Communities Around Jepara Regency Based on Ecotourism - Dena Ayu Aviantih; Sucihatiningsih dian wisika prajanti; Shanty Oktavilia (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
Tourism development has a direct effect on the community, the existence of tourism should have an impact on the conditions or conditions in the environment and around the tourism. In this case, marine tourism in Jepara Regency continues to be developed. The purpose of this study is to determine and analyze the impact of marine ecotourism development in Jepara Regency on the economic and social aspects of the community. The research methods employed include descriptive statistical analysis and the Analytical Hierarchy Process (AHP) method. The study's findings indicate that Jepara Regency's marine ecotourism has a significant impact on the economic and social aspects of the community. This is evident through increased income, the creation of new business opportunities, and an improved standard of living for the community. The social dynamics of the community are also affected, including employment status, community cooperation, and the establishment of new norms and values. Based on the AHP analysis, the recommended policies for managers and decision-makers in the development of marine ecotourism in Jepara Regency include efforts to enhance infrastructure that facilitates access to marine tourist destinations, the implementation of fiscal incentives and support for micro small medium enterprise (MSMEs) in the destination area, and achieving growth in visitor numbers while maintaining environmental quality by imposing penalties on tourists who harm the environment.